Studies with the Hanni's Portable Band Sawmill - Asthana, M. N.; Sethi, Y. R.; Sharma, C. M. (Indian Forester, 1966)
Time and cost studies have been done on the working of the Hanni's Portable Band Sawmill at Uttarkashi, U.P., with the object of studying its economics and efficiency. The study covered 215 logs of Pinus roxburghii over a period of 10 days in 1963. Daily out-turn and the cost of sawing per cubic foot, etc., as well as the hourly machine costs have been calculated. Regressions of various time intervals on log volumes have been worked out. The study shows that if the sawn cross sections are not limited to a few but the logs are sawn with a view to obtain maximum sawn out-turn, the efficiency of sawing would increase with the increased girth of logs. The average total sawing time per cft. Of sawn out-turn is 2.50 minutes with the present pattern of sawing, but this time could be minimised if sawing pattern is such as to produce maximum out-turn from a log.